Association between cognitive function and parameters of echocardiography and coronary artery angiography - Mohammad Hashemi; Zahra Teimouri Jervekani; Shahrzad Mortazavi; Mohammad Reza Maracy; Majid Barekatain (Arquivos de Neuro-Psiquiatria)
ABSTRACT We aimed to determine whether there is an association between cognition and the results of echocardiography and angiography, based on neuropsychological assessments. Methods: We assessed the cognition of 85 patients who had recently undergone coronary artery angiography. We calculated the Gensini score for the coronary artery disease index. We also performed echocardiography to find indices of cardiac functioning. Results: The lower left ventricular ejection fraction correlated with lower scores on visuospatial, executive function, processing speed/attention and verbal memory capacities (p ≤ 0.05). A higher Gensini score and left atrial size correlated with lower executive function and processing speed/attention (p ≤ 0.05). In the group of patients with an impaired cognitive state, higher Gensini scores correlated with decreased processing speed/attention (p = 0.01) and the e' index was associated with lower capacity of executive function (p = 0.05). Conclusion: Decreased processing speed/attention and executive function may correlate with cardiac dysfunction and coronary artery disease. The Color Trail Test may be considered for simple screening for cognitive problems in elderly patients with coronary artery disease or diastolic dysfunction.